JUMPA Vol.2 No.2 Juni 2015 HUBUNGAN PEMBERIAN INSENTIF DENGAN PRODUKTIVITAS KERJA KARYAWAN: HUBUNGAN PEMBERIAN INSENTIF DENGAN PRODUKTIVITAS KERJA KARYAWAN - Tjiauw Chiat Peng Fakultas Ekonomi Universitas Tarumanagara (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
In an increasingly tight business competition today, companies must have a competitive advantage compared to other companies. One of the benefits that should be owned by companies that qualified human resources. Seeing the importance of human resources in a company, it is expected that the company does not regard the employees as a factor of production. Thus the company must pay tribute to the work of employees in addition to the basic salary incentives in the form of material and non-material incentives in order to motivate employees to work more productively. Samples were employees of the sales department. The sampling method is done by non-probability sampling. While the sample selection technique is purposive sampling. Methods of data collection is done by interview and observation. Data analysis techniques performed by the correlation coefficient. Hypothesis testing results show that there is a relationship between the incentives to labor productivity.